2021
DOI: 10.1111/bjc.12292
|View full text |Cite
|
Sign up to set email alerts
|

The correlates of social phobia in OCD: Findings from a large clinical sample

Abstract: Objectives Obsessive‐compulsive disorder (OCD) is a debilitating psychiatric disorder, often complicated with comorbidities. Social phobia (SP) is the most frequent co‐occurring anxiety disorder in OCD, associated with increased clinical severity. However, no study had examined the relevance of interpersonal processes in this comorbidity, which are at the core of SP. This study characterized the clinical (i.e., symptom profile, age of onset, chronicity, and comorbidity), vulnerability (i.e., childhood trauma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…Specifically, we focused on OCD-related determinants such as age of onset, chronicity and initial severity level, which were previously identified as predictors of course (Dell’Osso et al, 2013; Sharma et al, 2014). We also examined the effect of common comorbidities on the long-term outcome of OCD, namely depressive symptoms (Quarantini et al, 2011) as well as the presence of social phobia, which was reported to be the most common anxiety disorder in OCD (Assunção et al, 2012; Lochner et al, 2014; Tibi et al, 2021). Furthermore, we explored the effect of the presence of tics and autism characteristics, which are interrelated clinical indictors that were associated with a specific, often poorer presentation of OCD (Anholt et al, 2009; De Vries et al, 2016; Hollander, 2005; Mito et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we focused on OCD-related determinants such as age of onset, chronicity and initial severity level, which were previously identified as predictors of course (Dell’Osso et al, 2013; Sharma et al, 2014). We also examined the effect of common comorbidities on the long-term outcome of OCD, namely depressive symptoms (Quarantini et al, 2011) as well as the presence of social phobia, which was reported to be the most common anxiety disorder in OCD (Assunção et al, 2012; Lochner et al, 2014; Tibi et al, 2021). Furthermore, we explored the effect of the presence of tics and autism characteristics, which are interrelated clinical indictors that were associated with a specific, often poorer presentation of OCD (Anholt et al, 2009; De Vries et al, 2016; Hollander, 2005; Mito et al, 2014).…”
Section: Introductionmentioning
confidence: 99%